2019
DOI: 10.1007/s13314-019-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Golovinomyces bolayi causes powdery mildew on Persian speedwell (Veronica persica) in Iran

Abstract: During October-November of 2017 and 2018, powdery fungal masses were observed on leaves of Persian speedwell (Veronica persica) on the campus of Tabriz University, East Azerbaijan Province, Iran. Infected leaves were collected and subjected to a taxonomic study. Based on morphological characteristics the fungus was identified as Golovinomyces orontii species complex. A phylogeny inferred based on ITS-rDNA sequence data clustered our isolate as Golovinomyces bolayi. Golovinomyces bolayi has recently been segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[ 10 , 32 ], according to the broad species concept for Golovinomyces [ 36 ]. However, some studies have reported G. orontii as the powdery mildew agent [ 9 , 25 ] and recognized that G. cichoracearum s. str. exclusively parasitizes plants in the tribe Cichorieae [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 32 ], according to the broad species concept for Golovinomyces [ 36 ]. However, some studies have reported G. orontii as the powdery mildew agent [ 9 , 25 ] and recognized that G. cichoracearum s. str. exclusively parasitizes plants in the tribe Cichorieae [ 37 ].…”
Section: Discussionmentioning
confidence: 99%